Structural, mechanical, and electronic properties of armchair and zigzag germanene nanotubes - Laranjeira, Jose A.S. [UNESP]; Denis, Pablo A.; Sambrano, Julio R. [UNESP] (Elsevier, 2024)
This computational study investigated germanene nanotubes (GeNTs) using density functional theory (DFT) simulations to comprehend their structural, mechanical, and electronic properties. The analysis includes armchairs and zigzag GeNTs with diameters from ∼7 to ∼221 Å. It explores their relative stabilities, band structures, density of states, effective mass carriers, and piezoelectric and elastic constants. As a result, it is highlighted that smaller nanotube diameters exhibit higher instability than larger ones due to increased structural strain produced by higher curvature. An intriguing behavior is observed for diameters greater than 25 Å, with negative strain energies. The quantum confinement effect significantly influences the electronic properties of GeNTs, leading to increased band gap energy for smaller nanotubes. The band gap energy of armchair nanotubes has a decreasing behavior as the diameter increases. In contrast, for zigzag nanotubes, the band gap energy increases to ∼13 Å diameter and then decreases, reaching a band gap energy of 0.08 eV. Regarding mechanical properties, smaller GeNTs exhibit significantly lower elastic constants (C11). As the diameter increases, C11 values converge around 114 GPa for both armchair and zigzag GeNTs. Only the zigzag GeNTs exhibit piezoelectricity. Carrier effective masses decrease with increasing diameter, enhancing carrier mobility for larger-diameter GeNTs. The herein-reported findings provide valuable insights into the properties of germanene nanotubes, demonstrating their promising potential for nanoscale device applications and inspiring further research and synthesis of germanene-related systems.
Keywords: Germanene; Graphene-like; Nanotube; Piezoelectricity; Strain energy